AN OVERVIEW OF THE INTERESTS AND PERCEPTIONS OF EARLY-STAGE RESIDENT DOCTORS TOWARDS ETHICS AND MEDICO-LEGAL TEACHING METHODS IN A FACULTY OF MEDICINE - Kulsum, Kulsum; Suryadi, Taufik (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2023)
Background: Ethics and medico-legal (EM) teaching must be carried out in a fun way so that resident doctors can more easily understand the material being taught. Conventional lecture methods are considered monotonous, so efforts are needed to find the best method that is most in demand by early-stage resident doctors so that learning objectives are achieved optimally. This study aims to describe the interests and perceptions of early-stage resident doctors toward EM teaching methods at the Faculty of Medicine, Universitas Syiah Kuala.Methods: This was an interventional study with a cross-sectional design conducted among early state resident doctors (n=54) with a self-administered online questionnaire. The participants of this study were early-stage resident doctors who had passed the EM courses. The participants were collected using the total sampling method. The participants were tested for seven teaching methods for seven EM materials. After all teaching methods were carried out, participants were asked to fill out a questionnaire.Results: A total of 54 participants were involved in this study. All resident doctors have a high interest and positive perception of all EM teaching methods. The respondent chose the film/video clipping method as the most interesting, followed by CBL, role play, MCD, jigsaw technique, conventional lecture, and narrative writing. The resident doctor's perception of the CBL teaching method was considered the most positive, followed by the film/video clip method, moral case deliberation, role play, jigsaw technique, conventional lecture, and finally narrative writing.Conclusion: The CBL method is most in demand by resident doctors because it directly discusses cases in educational settings, but the resident doctor considers the film/video clipping method to be the most enjoyable. The most favorite teaching method is expected to produce a better understanding of the material than others.